IMPACTS OF IMPERIALISM, CAPITALISM, AND ANTHROPOCENE IN THE COLONIAL WORLD - Shankar, Biklendu (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Environmental history is a new emerging field in academia. However, historians before the 1970s did not include nature as an essential aspect of analysis, especially in the academic field, due to the lack of primary sources that did not give them evidence of the nature aspect. So, we can say that natural elements were missing in the primary sources before the 1970s. However, when we look at the Colonial Archival data, we get evidence of deforestation, illegal exploitation of different resources, and the conquest of islands for the expansion of imperialism.